Quantitative Analysis of Lorazepam in Pharmaceutical Formulation Through FTIR Spectroscopy - Elaheh Konoz; Amir Hossein Mohsen Sarrafi; Marjaneh Samadizadeh; Samaneh Boreiri (E-Journal of Chemistry)
A Fourier transform infrared (FTIR) spectrophotometric method was development for the rapid, direct measurement of lorazepam in different pharmaceutical products. The method involves the off-line extraction of lorazepam with sonication and direct determination in the extract through peak height measurement in the 1704 cm-1 using a baseline correction between 1850 and 1550 cm-1. For standardization an external calibration line established from standard solutions of lorazepam in chloroform were used. The method provides a limit of detection of 0.0030 mg per tablet (n=5), a relative standard deviation (RSD) of 2.65% for 5 independent measurement of standard solution at a concentration level of 1 mgg-1. Result obtained by FTIR agrees with those obtained by a reference methodology based on ultraviolet spectrometry and thus the developed procedure offers a good alternative for the determination of lorazepam in commercial products.